2022
DOI: 10.1200/op.22.00412
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Screening Disparities in Persons Experiencing Homelessness

Abstract: PURPOSE: The purpose of this study was to assess prostate-specific antigen (PSA) testing rates in persons experiencing homelessness (PEH), identify factors associated with screening, and compare PSA screening rates in PEH with a matched cohort of persons not experiencing homelessness (non-PEH). MATERIALS AND METHODS: We identified 9,249 potentially eligible PEH cared for at a large metropolitan hospital system from an institutional registry of all patients who presented to the health care system as homeless fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Nevertheless, a recent study by Mayo et al. 22 found that having a primary care provider was the most significant factor associated with cancer screening utilisation.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, a recent study by Mayo et al. 22 found that having a primary care provider was the most significant factor associated with cancer screening utilisation.…”
Section: Discussionmentioning
confidence: 96%
“…15,17,20 The rate of cancer screening in the homeless population remains disproportionately low. [20][21][22] In the article that accompanies this editorial, Mayo et al 23 report on their findings from the first nonsurveybased study assessing prostate cancer screening in this population, 24,25 with few other studies assessing colon, breast, and cervical cancer screening. [26][27][28] In this study, the authors highlight the disparities that homeless individuals face and their impact on cancer screening adherence.…”
mentioning
confidence: 99%
“…The most significant factor associated with screening is access to a primary care physician, which had not been previously reported. 23 Several barriers are associated with decreased rates of prostate cancer screening including unemployment status and Medicaid insurance. Other studies have identified the following as barriers to cancer screening in this population: lack of an accompanying companion to procedures, 29 fear from prior trauma, [30][31][32] access, 17,20,24,33,34 low health literacy, 35 low rates of health education during clinical encounters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent JCO Oncology Practice paper found that homeless individuals had higher rates of substance abuse, less access to primary care services, less insurance coverage, and significantly lower rates of PSA screening. 3…”
mentioning
confidence: 99%